Characterization of citric acid-nicotinamide cocrystals prepared by the grinding method for enhanced stability of effervescent products - Roisah Nawatila; Ratih Ratih; Marisca Evalina Gondokesumo; Arya Rosandika; Willson Goh; Astrid Iga Wardani (Universitas Ahmad Dahlan, 2026)
Effervescent dosage forms contain acidic and basic components that react upon dissolution in water to releasing carbon dioxide (CO₂). In this study, citric acid was selected as the acidic component due to its affordability, high water solubility, and greater acidity than tartaric acid, while sodium bicarbonate was used as the basic component. However, citric acid is highly hygroscopic and can react prematurely with sodium bicarbonate under high humidity conditions (>20% RH, 25 °C), leading to undesirable premature effervescent reactions during manufacturing. To address this issue, this study aimed to modify a cocrystal of citric acid with nicotinamide as a co-former to enhance stability. Cocrystals were prepared using the grinding method at molar ratios of 1:1 (CN-Cocrystal 1:1) and 1:2 (CN-Cocrystal 1:2). The resulting solids were characterized by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR), scanning electron microscopy (SEM), and moisture interaction testing. PXRD results showed new crystalline phases for both cocrystals, with distinct diffraction peaks at 2θ values of 17.1132°; and 21.761° (1:1); and 16.9117°; 20.2717°; and 20.9566° (1:2). DSC thermograms exhibited new endothermic peaks at 107.01 °C (1:1); and 114.28 °C (1:2). FTIR spectra revealed shifts in the -OH group of citric acid and the -NH group of nicotinamide, indicating hydrogen bonding. SEM analysis confirmed distinct surface morphologies for the cocrystals compared to the pure compounds. Notably, moisture interaction testing demonstrated that both cocrystals maintained tablet diameter up to 120 minutes, while the control tablets showed significant dimensional changes. In conclusion, co-crystallization of citric acid with nicotinamide enhances moisture resistance and prevents premature effervescent reactions, with CN-Cocrystal 1:2 showing superior physical characteristics, making it a promising candidate for effervescent formulations.